HISTORY OF CHILDREN’S FURNITURE AND INTERIOR (Innovation in Woodworking Industry and Engineering design, 2026)
The importance of the development of a particular society has always been the focus it has on the weaker and the more vulnerable, some of whom are children. Often the banal phrase "Children is our Future" can be heard, but there is a huge amount of truth in it. That is why everything related to their proper development – physiological, mental, physical, etc. has been and will continue to be of the utmost importance since only a harmoniously developed child could be realized as a full-grown adult. This article will look at the historical development of children's furniture and interior in connection with this type of changes in society.